Knowledge and reference in empirical science - Jody, Azzouni (London Routledge United Kingdom, 2000)
Knowledge and Reference in Empirical Science is a fascinating study of the bounds between science and language: in what sense, and of what, does science provide knowledge? Is science an instrument only distantly related to what's real? Can the language of science be used to adequately describe the truth? In this book, Jody Azziouni investigates the technology of science - the actual forging and exploiting of causal links, between ourselves and what we endeavor to know and understand.
Keywords: Natural sciences; Science philosophy; Science methodology